Building caregivers’ emotional, parental and social support skills to prevent violence against adolescent girls: findings from a cluster randomised controlled trial in Democratic Republic of Congo - Stark, Lindsay (BMJ Glob Health, 2018)
INTRODUCTION: Parenting programmes are increasingly popular for reducing children’s exposure to interpersonal violence in low/middle-income countries, but there is limited evidence on their effectiveness. We investigated the incremental impact of adding a caregiver component to a life skills programme for adolescent girls, assessing girls’ exposure to violence (sexual and others) and caregivers’ gender attitudes and parenting behaviours. METHODS: In this two-arm, single-blinded, cluster randomised controlled trial, we recruited 869 adolescent girls aged 10–14 and 764 caregivers in South Kivu, Democratic Republic of Congo. Following a baseline survey, participants were divided into 35 clusters based on age, language and location. Eighteen clusters were randomised to the treatment arm and 17 clusters to the wait-list control arm. Adolescent girls in both arms received 32 life skills sessions; caregivers in the treatment arm received 13 complementary caregiver sessions. The primary outcome was girls’ self-reported exposure to sexual violence in the last 12 months; secondary outcomes included self-reports of specific forms of sexual violence, physical and emotional violence, transactional sex, child marriage for girls and parenting behaviours for caregivers. Intent-to-treat and per-protocol analyses were conducted. RESULTS: At 12 months of follow-up, the intervention showed no impact on sexual violence (adjusted OR=0.95; 95% CI 0.65 to 1.37) or any secondary outcomes for girls. The intervention was associated with improved supportive parenting behaviours. Protocol adherence was also associated with improvements in these outcomes. CONCLUSION: While the caregiver curriculum improved some parenting outcomes, additional programmatic adaptations may be needed to reduce adolescent girls’ violence exposure in humanitarian settings. TRIAL REGISTRATION NUMBER: NCT02384642.